DESIGN AND BUILD AN ANDROID-BASED CUSTOMER MENU RECORDER APPLICATION ON BENU COFFEE SHOOP USING AGILE METHODS - Putri, Wita Atika; Irwan, Dedy; Lubis, Husni (Cattleya Darmaya Fortuna, 2024)
Information technology is a process from obtaining data to processing and analyzing the data so that it is stored in various ways to create or produce quality information. Currently, the development of information technology is very rapid and fast, including in Indonesia itself, therefore this research explores the Android-based design